OPTIMIZING EVENT MARKETING EFFECTIVENESS : A COMPARATIVE COMPETITOR ANALYSIS USING THE MARKETING MIX 7PS - Devia Mahartika Anggini; Atik Aprianingsih (LPPM STIE Muhammadiah Bandung, 2025)
Event marketing has become an important way to get the right people to your business and improve your brand's position in the fast-changing digital economy and business-to-business (B2B) markets. The Marketing Mix 7Ps framework, which includes Product, Price, Place, Promotion, People, Process, and Physical Evidence, is used in this study to look at the event marketing strategies of PT. Mitra Generasi Digital (MGDverse). After that, the strategies are compared to those of competitors referred to as Company A and Company B in this study. Note: The names of competitors used in this research are pseudonyms and do not represent the actual names of the companies involved. The study looks at the pros and cons of MGDverse's strategy using both qualitative data from internal documents and interviews, as well as secondary data from competitor websites and industry reports. The results show that MGDverse is very professional in terms of operations and has a wide variety of events, but its registration and promotion efforts are not as effective as its competitors', which makes it harder for people to find and attend events. The study also explores how to use platform-specific outreach and personalized messaging to get the most leads for the least amount of money (CPL), improve lead quality, and make campaigns more effective. The main suggestions are to improve digital registration integration, increase targeted promotions, tailor content for specific audiences, and strengthen one-on-one communication. These improvements could give MGDverse an even bigger edge over its competitors and help the digital marketing events market in Indonesia grow over time.